Isomerization of endo- to exo-tetrahydrotricyclopentadiene over alumino-silicate catalysts. (1st June 2018) - Cho, Young-Hoon; Kim, Chan Hun; Lee, Seong Ho; Han, Jeongsik; Kwon, Tae Soo; Lee, Kwan-Young
Graphical abstract: Abstract: Isomerization studies have been carried out to improve the physical properties of tetrahydrotricyclopentadiene (THTCPD), which has been attracting attention as a liquid fuel for aviation and military use. However, there have been few studies on heterogeneous catalysts for environmentally friendly process until now. In this study, the isomerization activities over various alumino-silicate catalysts (ZSM-5, MOR, HY, Cu-HY, Al-MCM-41) were evaluated using a batch reactor, and the catalytic properties suitable for the reaction were investigated. The catalytic performances were significantly affected by the microchannel or pore size, acid strength and acid type of each catalyst. N2 adsorption-desorption, NH3 -temperature-programmed-desorption and pyridine Fourier-transform-infra-red analyses indicated that the pore size of the catalyst and the acid strength on the catalyst surface affected the conversion rate of endo- THTCPD, and the type of acid on the catalyst surface affected the exo- THTCPD selectivity. The HY catalyst showed the highest yield and productivity among all of the catalysts evaluated. The study of the time-on-stream reaction over the HY catalyst showed that some by-products continued to increase during the reaction time, and there was an optimum reaction time to obtain the highest yield.